OPERATIONS MANAGEMENT WITH AN ENTREPRENEURIAL VIEW - A RESEARCH PROJECT ABOUT OPERATIONS MANAGEMENT STRATEGIES IN ESTABLISHED TRANSPORT AND LOGISTICS COMPANIES IN THE UK, PORTUGAL AND ANGOLA TO FIND OUT WHAT ROLE INNOVATION PLAYS IN TRANSPORT AND LOGISTICS OPERATIONS - Bravo da Rosa, V (2014)
The economic market and development in the 20th century is globally more competitive and fast-paced than ever before. Companies, enterprises and businesses of any size and format need to adjust their corporate strategies in order to keep up with the rest of the business world. Innovation is the way forward in the current economic market, but not all business owners have yet recognised the need for innovative thinking and innovative strategies. This academic research project is intended to show and evaluate existing theoretical frameworks in practice. The following report starts off with a literature review about the already existing theoretical knowledge about innovation, innovation management and the role it plays in the operational strategies applied in existing transport and logistics companies in a selection of different countries. Three countries have been chosen – namely the UK, Portugal and Angola – in order to compare the existing levels of innovation and innovative operational strategies in existing T&L enterprises. In the second part of this report the methodology of the quantitative and qualitative research, that has taken place, will be explained. The third part is about the important question what role innovation plays in the daily operations of T&L companies and why it is so important. What factors drive innovation in T&L? On one hand existing knowledge and facts will be reviewed, and on the other hand local research and observations in a number of selected T&L companies in the UK, Portugal and Angola will be evaluated. During this analysis the findings from the three different countries are compared to establish equalities and differences between them. Another question is what the future of innovative operations management in the area of transport systems in each country looks like? Conclusively, the findings are summarised and the role of innovation in operational strategies in T&L identified and how the success of ITS can be measured and evaluated with regards to it being a very recent development and extensive research has not been carried out.